Relação da espessura e rigidez do diafragma e do músculo reto abdominal por ultrassonografia (ARFI) e da composição corporal com exposição ácida do esôfago em idosos - Costa, Jesus Irajacy Fernandes da (2022)
Ultrasonography and elastography are inexpensive, practical, irradiation-free and feasible tests for evaluating tissue morphology and stiffness. These exams are reported in an increasing number of studies despite the evolution of imaging methods. They can be applied to striated muscles, thus allowing the study of the costal diaphragm. The crural diaphragm (CD) acts as an extrinsic sphincter on the esophagogastric junction and it is an important component of the anti-reflux barrier. Some patients with reflux esophagitis have an anatomical and functional deficit of the CD. Skeletal muscle deficit is more prevalent in the elderly. The aim of this work was to evaluate the relationship between the thickness and stiffness of the costal diaphragm and the rectus abdominis muscle with gastroesophageal reflux disease (GERD). The methodology applied consisted of a cross-sectional study with a quantitative approach carried out with elderly people from the Geriatrics Outpatient Clinic of the Walter Cantídio University Hospital. The sample consisted of 26 volunteers, female gender was predominant and average age of 72 years. Patients underwent assessment of typical and atypical GERD symptoms, physical examination to collect anthropometric measurements, quantification of body water by dilution of deuterium in saliva, abdominal ultrasound/elastography (diaphragm, liver and rectus abdominis muscle), and 24-hour esophageal pH monitoring. The research protocol was approved by the Research Ethics Committee of the Federal University of Ceará (UFC) and the volunteers signed an informed consent form. The volunteers were divided into two groups regarding acid exposure (AE) of the distal esophagus: AE ≤ 4% (n=19) and AE > 4% (n=7). There was no correlation between diaphragm and rectus abdominis muscle thickness and body water composition with esophageal acid exposure. The group of individuals with AE greater than 4% had lower diaphragm stiffness on inspiration when compared to the group with AE below 4% (mean = 4.06 ± 0.80 versus 3.43 ± 0.29; T test: p = 0.008). The group of individuals with acid exposure above 4% had lower rectus abdominis muscle stiffness on contraction than the group of individuals with acid exposure time below 4% (mean = 5.93 ± 1.52 versus 4.45 ± 0.78; Test t: p = 0.004). Therefore, there is evidence that the diaphragm stiffness on inspiration and the stiffness of rectus abdominis muscle contracted are associated with a greater AE, and it is possible that they could be used as biomarkers for this condition in the elderly.